EVENTS AND FIGURES OF THE UKRAINIAN REVOLUTION OF 1917–1921 IN THE JOURNALISM OF YEVHEN MALANYUK (Південний архів (історичні науки), 2022)
Purpose. The task of the article is to analyze the essayist and journalism of Yevhen Malanyuk, which concerns significant, interesting and at the same time insufficiently known episodes of the Ukrainian Revolution, in which Yevhen Malanyuk was kept secret. Also the subject of the study are biographical sketches of officers of the UPR army. The analysis of E. Malaniuk’s creative heritage may be of great interest to researchers of liberation struggles in view of E. Malaniuk’s significant awareness of important and little-known nuances of making fateful decisions for Ukrainian history. Methods. The state of scientific development of the problem encourages the continuation of the analysis of E. Malanyuk’s literary heritage in the historical context. His creative work, dedicated to the events of the Ukrainian revolution, can be classified according to several approaches: the genre of works and their problems. Let’s start with the genre classification. E. Malaniuk’s works devoted to the events of the Ukrainian revolution are journalism, biographical essays, and poetry. For the analysis of Yevhen Malanyuk’s texts we use the method of hermeneutic analysis of his texts, approaches of biography and comparative studies. Interdisciplinary tools will also be used, as the study is based on the analysis of biographical and creative fragments of the biography of the poet, publicist, participant in the liberation struggle. Results. E. Malanyuk’s journalism, essays, and poetry related to the era of liberation struggles are analyzed. The assessment of the author, whose work is the subject of the article, to different periods, phenomena, personalities of the Ukrainian revolution of 1917–1921. In particular, V. Tyutyunnyk, S. Petliura, E. Mishkovsky, V. Sinclair. E. Malaniuk’s view on the causes of the Kiev catastrophe, Ukrainian-Polish and Ukrainian-Russian interstate relations in 1919, the nuances of decision-making on the Warsaw Pact and the organization of the First Winter Campaign, the policy of the Hetmanate and the Directory in the field of military construction are analyzed. Conclusions. E. Malaniuk’s creative legacy remains relevant for researchers, both historians and philologists. And his advice is a valuable asset for Ukrainian commemoration and the development of modern information policy in the Russian-Ukrainian war of the XXI century.
Keywords: Yevhen Malanyuk, Ukrainian revolution, journalism, essays, Kyiv catastrophe, First Winter Campaign, Warsaw Pact, commemoration.